Thermal Self-Sufficient Operation of Hydrogen Production from Used Vegetable Oil - Sathaporn Niamboonnum (AIDIC Servizi S.r.l., 2021)
This work aims to investigate the hydrogen production from used palm oil and used soybean oil through autothermal reforming (ATR). Thermodynamics analysis of this process was performed by using Aspen plus V9 simulation software. The gas compositions at equilibrium were calculated by using the Gibbs free energy minimization method. The hydrogen production process was composed of ATR reactor, high-temperature water gas shift (HT-WGS), low-temperature water gas shift (LT-WGS) and absorber. Considering the optimal conditions of each unit operation, it was found that the maximum hydrogen production can be provided when ATR reactor was operated at temperature of 580 °C, atmospheric pressure, steam to carbon (S/C) molar ratio of 10 and oxygen to carbon (O/C) molar ratio of 0.1. HT-WGS and LT-WGS reactors should be operated at temperature of 300 °C and 200 °C. For the absorber, the optimal conditions were at 40 atm with 6 kmol/h of MDEA solution at 35 °C. Under these operating conditions, hydrogen can be generated as 2.56 kmol/h or 99.7 mol%. Then, the hydrogen production under thermal self-sufficient operation was studied. The simulation result indicated that the ATR reactor should be operated at temperature of 580 °C and atmospheric pressure with S/C molar ratio of 4.5 and O/C molar ratio of 0.47 to achieve thermal self-sufficient operation. When the ATR reactor was operated under these operating conditions whereas the operating conditions of HT-WGS, LT-WGS and absorber were constant, it was found that hydrogen with molar flow rate of 1.71 kmol/h (99.7 mol%) can be provided.